The Influence of School Management on The Implementation of The Merdeka Belajar Curriculum - Fathurrahman, Fathurrahman; Arifin, Bambang‎ Syamsul; Muhyi ‎, Abdul; Huda, Miftahul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This research aims to analyze the change of the curriculum into the Merdeka curriculum. The research uses quantitative methods. Data was collected by interviewing the principal and distributing questionnaires to teachers, curriculum development teams, and school management who prepared this curriculum to be developed and collaborated. The implications of this study affect various policies managed by schools and the addition of existing values in institutions, such as the character value of the Pancasila student profile. The results for the readiness variable for curriculum changes at SMPIT Nurul Islam are sufficient qualifications. The influence of school management from the results of the Fcount states that 76.4% of the X variable affects the Y variable. The school management has a strong influence on readiness in curriculum changes with results which can be interpreted that the more school management prepares carefully and sustainably, the more curriculum changes will get better and more successful so that it affects the quality of schools and the quality of learning.